Spiritual Coping in the Process of Home Care Among Family Caregivers: A Qualitative Longitudinal Study in Germany - Kubitza, Jenny; Steinmaier, Verena; Lauer, Natascha; Pendergrass, Anna; Frick, Eckhard (Health & Social Care in the Community, 2025)
Spirituality helps family caregivers (FC) cope with the challenges of home care. FCs use spiritual resources such as hope, faith, or reflection to develop a mindful relationship with themselves, experience meaning, and accept the new life situation, which reduces negative emotions and strengthens their resilience. There is currently a lack of studies investigating how spirituality among FCs changes over time in the care situation. More knowledge about the dynamics of spirituality among FCs is needed to support them appropriately. This longitudinal qualitative study employs an interpretative phenomenological design to describe and understand the spirituality of FCs in the process of home care. In Germany, 24 FCs were interviewed between August 2022 and July 2023, and 11 were interviewed a second time between November 2023 and February 2024. Most FCs cared for cognitively impaired relatives, while the remaining FCs cared for family members with physical or psychosomatic impairments. The resulting data were first evaluated using content analysis, resulting in a category system that was analyzed using a phenomenological approach to get an overall story. The study adheres to COnsolidated criteria for REporting Qualitative research (COREQ). The analysis revealed that FCs use spirituality to experience meaning in care and harmonize it with their meaning in life. To achieve this, FCs experience a spiritual process with five stages: (1) preserving proven values, (2) spiritual trouble, (3) spiritual crisis, (4) reflection on one’s own life, and (5) spiritual development and acceptance. The findings show that the FCs have different spiritual needs and resources in the stages; while the FCs use proven spiritual strategies at the beginning of care, they develop a new form of spirituality over time. This development helps the FCs to cope with and accept their life situation. Healthcare professionals can use the stages as a guide to understand the spiritual needs of FCs and offer them relevant resources.
CRIS-Team Scopus Importer:2025-11-21
Keywords: content analysis; family caregivers; longitudinal study; phenomenology; qualitative research; spirituality